A Study Of Versions Of The Epic “Alpamish” - Kalandarova Dilafruz Abdujamilovna (Genius Journals, 2025)
This article examines the Kazakh and Karakalpak versions of the most famous Uzbek folklore epic “Alpamish”, and discusses their similarities and differences. Several hypotheses regarding the names of the regions where the epic takes place are analyzed.
Keywords: epic; bakhshi; performance; variant